OPTIMIZATION OF ANALOG-TO-DIGITAL CONVERSION IN TELECOMMUNICATION SYSTEMS - Давлетьянц, О.; Борейчук, О.; Василенко, О.; Євсеєв, О.; Кривоус, В. (Science-based technologies, 2011)
To reduce miscalculations of analog-to-digital conversion method it is offered to use the preliminary method ofnonlinear transformation which describes the distribution function of the signal being converted. The examplesand results of statistical modeling of transformation processes are given below.